Case report: A novel nonsense mutation in the MARVELD2 gene causes nonsyndromic hearing loss in a China family - Huang, Chuican; Huang, Zhenning; Wang, Ping; Wu, Xijing; Zhou, Qiaomiao; Ding, Jun; Luo, Qing; Wu, Weijia; Fan, Xialin; Fan, Lichun (Frontiers in Genetics, 2024)
The MARVELD2 gene is located on chromosome 5q13.2 and is associated with autosomal recessive nonsyndromic hearing loss (OMIM: # 610572). In this study, we identified and reported a novel nonsense mutation in MARVELD2 c. 663G > A in a Chinese family. We collected peripheral venous blood from 19 members of the affected family and performed whole exome sequencing to analyze the mutation genotype. A single-nucleotide mutation was detected in MARVELD2. Five individuals in the family carried the MARVELD2 c.663G>A mutation; one of them was homozygous and showed severe congenital deafness and language impairment. The next-generation sequencing results were validated by Sanger sequencing. This study expands the spectrum of MARVELD2 mutations that cause nonsyndromic hearing loss and provides insights into the molecular pathogenesis underlying deafness. This finding has important implications for genetic screening, diagnosis, counseling, and research of deafness-related genes.